Evaluasi Penerapan Sistem Pengendalian Internal Dalam Pencegahan Kecurangan Persediaan Dengan Menggunakan Kerangka Kerja COSO - Desi Krisdianti; Iyeh Supriatna (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this final project is to find out and evaluate the application of internal control over supplies at one of the UMKMs engaged in the culinary field, namely Limarasa Coffee Shop. This research was conducted using a qualitative descriptive method. The method for conducting internal control is to use the COSO) approach which is supported by data analysis techniques in the form of a control matrix. In this research, the types of data used are primary data and secondary data. The techniques used in the process of collecting data are through interview techniques, observation, documentation, and questionnaires. The results obtained from the research show that Warung Kopi Limarasa has implemented an internal control system over inventory based on the framework of the Committee of Sponsoring Organizations of The Treadway Commissions (COSO). However, the internal control applied has not been effective because there are still some elements of internal control that have not been implemented so that it can create opportunities for inventory fraud.